Experimental study of sandstone crack propagation behavior under different seepage pressures - ZHANG Li-ming; WANG Zai-quan; ZHAO Tian-yang; CONG Yu (Rock and Soil Mechanics, 2022)
To study the characteristics of sandstone crack propagation under hydraulic coupling, sandstone laboratory tests were conducted under different seepage pressures and confining pressures. Under the same effective confining pressure, it is shown that the rock brittleness index becomes higher as the seepage pressure increases, while the crack initiation stress, the crack damage stress, and the peak stress decrease gradually. The initial volumetric strain of the crack decreases, and the volumetric strain of crack propagation decreases firstly and then increases afterward. The growth rate of the crack axial strain and the crack circumferential strain are both increasing that corresponding to the damage stress and the peak stress, however, no obvious relation is observed between the growth rate of the crack volume strain and the seepage pressure. Under the same seepage pressure, the initiation stress, damage stress, and peak stress gradually increase as the effective confining pressure increases. In addition, the growth rates of the crack axial strain, circumferential strain and volumetric strain increase gradually during deformation that corresponds to the crack initiation stress, damage stress and peak stress, respectively. When comparing the different growth rates of crack strain for a tested sandstone specimen, it is found that the strain growth rates have the following order: the crack axial strain > the crack circumferential strain > the crack volume strain.